2005
DOI: 10.1007/s00038-005-4089-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of knowledge, attitudes and behaviour regarding smoking among Estonian and Finnish physicians

Abstract: Physicians' own smoking patterns and quitting behaviour are important because physicians serve as models for their patients and play a key role in the reinforcement of smoke-free health facilities. These results remain a challenge to medical educators, especially in Estonia. Estonia needs to improve medical education in terms of motivating physicians to ask about the smoking patterns of their patients and of training medical students and resident physicians to counsel their patients to stop smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 17 publications
5
31
0
1
Order By: Relevance
“…The prevalence of smoking among physicians has decreased during the last decades in many places [8,13,28,29]. In these countries the population appears to be well informed about the dangers of smoking and physicians seem to respond by giving up smoking more frequently than other individuals, resulting in this important drop in prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of smoking among physicians has decreased during the last decades in many places [8,13,28,29]. In these countries the population appears to be well informed about the dangers of smoking and physicians seem to respond by giving up smoking more frequently than other individuals, resulting in this important drop in prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Physician smokers appear to be less willing to inquire about tobacco use, to advise cessation, and to provide evidencebased assistance when compared to their non-smoking counterparts [13][14][15][16][17][18][19][20][21]. In countries with lengthy histories of anti-tobacco activity, such as Canada, the USA, Sweden, Australia, and the UK, this is not a major problem since physician smoking rates are very low.…”
Section: Introductionmentioning
confidence: 99%
“…However, smoking rates among HCPs in Ireland are still markedly lower than other countries (41% among doctors in China) 29 . Previous studies found HCP smoking status was associated with willingness to engage with their patients regarding smoking [4][5][6][7][8][9][10][11][12][13] . In the current study there was no association between smoking status and routine recording of status, routine advising, referring to smoking cessation services or feeling prepared to assist.…”
Section: Prevalencementioning
confidence: 99%
“…First to support the health of this group we must ensure the health system they work in continues to promote their own health generally and more specifically by providing a smoke free workplace and supporting those trying to quit smoking. Secondly the smoking status of physicians and 'health staff' appears to impact upon their willingness to engage with patients regarding tobacco Tobacco Prevention & Cessation use [4][5][6][7][8][9][10][11][12] . An international survey found that physicians who smoked were less likely to initiate cessation interventions in comparison to their non-smoking counterparts 13 .…”
Section: Introductionmentioning
confidence: 99%